Energy Consumption Assessment on Industrialised Building System (IBS) - Nadia, Zaini; Siti Halipah, Ibrahim; Nur Fadilah, Darmansah; Abdul Wafi, Razali; Sitti Diana, Tamjehi; Afzan Ahmad, Zaini; Hasmida, Hamza; Sharifah NurFarhana, Syed Sahimi (CIDB Malaysia, 2020)
Malaysia Government mission towards development of low carbon cities in reducing carbon emission by 40% by year 2020. Therefore, our construction industry plays an important role and gives negative impacts on the environment. Factors of embodied energy and carbon emission are important in selecting construction method by considering the low carbon type of construction material to be used during the construction process. This paper presents an analysis of Embodied Energy and carbon emission in a building that used IBS and conventional method to achieve sustainable construction in Malaysia. All data was recorded and analyse using a commercial Life Cycle Assessment (LCA) tool called Carbon Calculator. The study includes IBS component; precast concrete wall panel, column, beam and half slab and cast in situ components; burn clay bricks, reinforced concrete slab, column, and beam. The results are presented in terms of carbon dioxide equivalent (CO2E) of construction materials and comparison analysis is made between IBS and Conventional method. The results obtained from Carbon Calculator due to manufacture and installation of components show a that IBS method consumed 26.93 CO2E/m2 and conventional method offers 39.57 CO2E/m2. By comparing IBS and conventional method, it is found that the average of total energy consumption due to construction materials was 33.25 CO2E/m2 and involved 31.94% reduction in comparison with conventional method. Therefore, for further building construction’s practice in relation to type of construction method it is recommended to be below the average amount of energy consumption 33.25 CO2E/m2 (50%) and any values obtained above the average amount is considered not being able to adopt sustainable building practice. Generally, it can be concluded that implementation of IBS method can be regard as a potential in reducing the amount of embodied energy and carbon emission compared to conventional method.